Mubazir dalam Tafsir dan Praktik Sosial: Studi Living Quran pada Fenomena Food Waste Saat Resepsi Pernikahan - Muh. Mukhlish Abidin; Umi Farihah Arif (Jurnal Ragam Pengabdian, 2026)
The phenomenon of food waste at wedding receptions is a common social practice. This practice is interesting to study because it directly contradicts the Quranic prohibition against wasteful behavior and israf. This article aims to analyze how verses about wasteful behavior are understood, negotiated, and presented in the social practices of society at wedding receptions. This research uses a qualitative method with a living Quran approach through participatory observation and in-depth interviews with invited guests, reception organizers, and community leaders. The results show that society recognizes the prohibition on wasteful behavior, but specifically at wedding receptions, this understanding is negotiated with ethics, social norms, and the logic of abundance and consumer hedonism. From a living Quran perspective, this phenomenon demonstrates that the Quran lives in the public consciousness contextually and partially, not always in the form of textual adherence. This article contributes to the development of social interpretation studies by emphasizing the importance of contextual reading of Quranic consumption ethics in the cultural practices of contemporary Muslim communities